Nanostructures Formed by Custom-Made Peptides Based on Amyloid Peptide Sequences and Their Inhibition by 2-Hydroxynaphthoquinone - Mannem, Radhika; Yousuf, Mohammed; Sreerama, Lakshmaiah (Frontiers in Chemistry, 2020)
Extensive research on amyloid fibril formations shows that certain core sequences within A peptide play an important role in their formation. It is impossible to track these events in vivo. Many proteins and peptides with such core sequences form amyloid fibrils and such A sheet mimics have become excellent tools to study amyloid fibril formation and develop therapeutic strategies. A group of peptides based on amyloid peptide sequences obtained from PDB searches, where glycine residues are substituted with alanine and isoleucine, are tested for aggregation by SEM and ThT binding assay. SEM of different peptide sequences showed morphologically different structures such as nanorods, crystalline needles and nanofibrils. The peptides were co-incubated with HNQ (a quinone) to study its effect on the process of aggregation and/or fibrillation. In conclusion, this group of peptides seem to be A sheet mimics and can be very useful in understanding the different morphologies of amyloid fibrils arising from different peptide sequences and the effective strategies to inhibit or anneal them.